Non-Relativistic and Low Mach Number Limits of a Compressible Full MHD-$P1$ Approximate Model Arising in Radiation Magnetohydrodynamics (Journal of Mathematical Study, 2021)
In this paper we study the non-relativistic and low Mach number limits ofstrong solutions to a full compressible MHD-$P1$ approximate model arising in radiationmagnetohydrodynamics. We prove that, as the parameters go to zero, the solutionsof the primitive system converge to that of the classical incompressible magnetohydrodynamicequations.
Keywords: Full MHD-$P1$ approximate model; non-relativistic and low Mach number limit.